2021
DOI: 10.3390/catal11121479
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Quaternary Ammoniums Derived from Dehydroabietylamine: Synthesis and Application to Alkynylation of Isatin Derivatives Catalyzed by Silver

Abstract: Abietic acid and its derivatives have broadly been used in fine chemicals and are renewable resources. Its inherent chiral rigid tricyclic phenanthrene skeleton is unique. Its utilities in asymmetric catalysis remain to be explored. A series new amide-type chiral quaternary ammoniums bearing dehydroabietylamine were designed, and prepared by two convenient steps. Acylation of dehydroabietylamine with bromoacetyl chloride afforded amide holding bromoacetyl group in higher yields using triethyl amine as base. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 103 publications
0
17
0
Order By: Relevance
“…In 2016, Liu reported an asymmetric alkynalation of isatins catalyzed by a CuI/guanidine catalyst [12a] . Followed by this pioneered work, vairous efficent catalytic systems were developed, such as CuI/chiral phosphine ligand, [12b] CuOTf/bisoxazolidine, [12c] CuOTf/chiral aminophenol sulfonamide ligand, [12d] AgOAc/chiral phase‐transfer catalyst, [12e,f] AgBF 4 /bifunctional amidophosphine‐urea catalyst [12g] and Co(OAc) 2 /bisoxazolinephosphine catalyst [12h] . Besides, our group coined a Zn(OTf) 2 /chiral hydroxyl oxazoline ligand catalyst system to catalyze the generation of 3‐alkynyl‐3‐hydroxy‐2‐oxindoles [12i] .…”
Section: Figurementioning
confidence: 99%
“…In 2016, Liu reported an asymmetric alkynalation of isatins catalyzed by a CuI/guanidine catalyst [12a] . Followed by this pioneered work, vairous efficent catalytic systems were developed, such as CuI/chiral phosphine ligand, [12b] CuOTf/bisoxazolidine, [12c] CuOTf/chiral aminophenol sulfonamide ligand, [12d] AgOAc/chiral phase‐transfer catalyst, [12e,f] AgBF 4 /bifunctional amidophosphine‐urea catalyst [12g] and Co(OAc) 2 /bisoxazolinephosphine catalyst [12h] . Besides, our group coined a Zn(OTf) 2 /chiral hydroxyl oxazoline ligand catalyst system to catalyze the generation of 3‐alkynyl‐3‐hydroxy‐2‐oxindoles [12i] .…”
Section: Figurementioning
confidence: 99%
“…It was found that N-benzyl isatin 2k can be employed in this transformation, affording the corresponding products 4ka and 4kb in high yields with good enantioselectivities. The mechanism of this Ag-catalyzed alkynylation of isatin derivatives was proposed on the basis of the experimental results as well as a working hypothesis from the literature, 12,13,15 as shown in Scheme 3. We speculated that a silver alkynilide ion pair intermediate A with a chiral quaternary ammonium catalyst (Q + Br − ) can be formed by the coordination of terminal alkyne 3a with Ag(I) and deprotonation.…”
mentioning
confidence: 99%
“…■ EXPERIMENTAL SECTION General Information. 1 H and 13 C NMR data were acquired on a Bruker AV-500 MHz spectrometer. HRMS were obtained from an Agilent 6520 Q-TOF LC/MS instrument.…”
mentioning
confidence: 99%
See 2 more Smart Citations